Marrying A Pregnant Woman From The Perspective Of Islamic Legal Philosophy - Zani Munawir S (ISNU Sumatera Utara, 2024)
The phenomenon of marriage of pregnant women outside of marriage is a complex issue from the perspective of Islamic law. The Compilation of Islamic Law (KHI) stipulates that a pregnant woman can marry the man who impregnated her without waiting for the birth of the child. However, there is a problem when a pregnant woman marries a man who is not the biological father of the child she is carrying, which raises questions about the validity of the marriage and the legal status of the child. In the context of Islamic legal philosophy, marriage is not just a social contract, but also has moral and spiritual dimensions that must be maintained in order to achieve welfare. This study aims to examine the marriage of pregnant women from the perspective of Islamic legal philosophy in order to find the principles of justice and legal benefits. The method used is qualitative with a literature study approach, analyzing fiqh books, laws and regulations, and related literature. The results of the study show that although the KHI allows the marriage of pregnant women, the jinayah aspect in cases of adultery is still ignored, so a more comprehensive legal reconstruction is needed. The conclusion of this study confirms that the regulation of the marriage of pregnant women must consider aspects of legal protection, justice, and moral responsibility so as not to open loopholes for the increasingly widespread practice of adultery.